Lingua Franca, Multilingualism, and Ecological Discourse: A Critical Ecolinguistic Perspective on Language and Environmental Interaction in Indonesia - Rajagukguk, Rosdiana (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study is to describe and analyze how much the lingua franca is related to the intersection of language and environment through ecolinguistics and multilinguism associated with polyglotism that can translate the concept of English well.Originality This research explains the relationship of lingua franca to the intersection of language and environment through ecolinguistics and multilinguism associated with polyglotism that can translate the concept of English well, where the research method is carried out using qualitative descriptive analysis using systematic review analysis, and data retrieval methods are carried out using literature studies and documentation studies.Design/methodology/approach The research method used in this research is descriptive qualitative research method through systematic review method from literature study and documentation study.Findings Based on the results of this study, it can be concluded that the relationship between lingua franca, intersection of language and environment, ecolinguistics, multilingualism, and kepiliglotism involves a complex understanding of how language, culture, and environment are interrelated, where the use of lingua franca can affect how traditional knowledge about the environment is translated, maintained, or even lost in a multilingual society, multilingualism, particularly in the context of lingua franca, reflects the complex relationship between language and culture in diverse societies, and polyglotism, or the ability to speak several languages with a high degree of proficiency, often includes the use of a lingua franca as one of the many languages the individual speaks.Implementation.Through the approaches of ecolinguistics, multilingualism and kepiliglotism, we can understand the complexity of the relationship between language, culture and the environment, as well as the implications of using lingua franca in this context. This makes it possible to develop more effective and sustainable communication strategies in the quest for environmental preservation and global sustainability.